P21-Activated Kinase 1 Overactivates in Eutopic Endometrium of Adenomyosis. (September 2019) - Zuo, Weiwen; Wu, Xiaoyi; Liu, Haiou; Xu, Congjian
Adenomyosis is a common gynecological disease, characterized by the existence of endometrium in the myometrium. The pathogenesis of adenomyosis is not fully understood. P21-activated kinase 1 (PAK1) is an effector of small Rho GTPases including CDC42 and RAC1 and plays various roles in cellular biology, especially cytoskeletal remodeling. This study aimed to evaluate whether the expression and activation of PAK1 in adenomyosis were different from normal. Immunohistochemistry was performed to evaluate the expression of PAK1 and its active form phosphorylated-PAK1 (pPAK1) semi-quantitatively in women with and without adenomyosis. Immunofluorescence was performed to locate the distribution of pPAK1. This study found that PAK1 in eutopic endometrium of adenomyosis was overactivated compared to normal. Phosphorylated-PAK1 assembled along the apical surface of glandular cell membrane. In ectopic lesions, PAK1 expression decreased and its activation returned to the baseline. The expression of pPAK1 correlated with the frequency of reproduction. These findings suggest that PAK1 overactivation in the endometrium may be an important event during the development of adenomyosis, meanwhile, decreased phosphorylation may assist to form lesions.